The role of customer satisfaction as a mediating mechanism in linking service quality and selling price to business profit: evidence from generation z consumers in micro retail - Nerry Arista; Suhardi Suhardi; Mat Amin (Economic: Journal Economic and Business, 2026)
This study aims to analyze the influence of service quality and selling price on business profits through customer satisfaction as a mediating variable, focusing on Generation Z consumers in the context of micro-retail businesses. The study used a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method on 100 respondents. The results showed that selling price and service quality have a positive and significant effect on customer satisfaction, with selling price having a more dominant influence. Furthermore, customer satisfaction was shown to have a strong and significant influence on business profits. However, the direct effect of selling price and service quality on business profits was not significant. Mediation analysis showed that customer satisfaction fully mediates the relationship between selling price and service quality on business profits. These findings confirm that customer satisfaction is a key mechanism linking marketing strategy to financial performance. This study contributes to broadening the understanding of the role of mediation in the context of micro-businesses and provides practical implications for business actors in increasing profitability through strategies oriented towards customer satisfaction.